CORAK TAFSIR AL-QURAN IBNU „ARABI - Cecep Alba (Fakultas Seni Rupa dan Desain ITB, 2010)
Sufism, both as doctrine and as a science is still underestimated by most Muslims. No less in the disintegration, Zahir expert scholars (jurists) have blamed the mysticism and even claim the Sufis infidel. According to them, Sufism is not only not in the Koran, even deviate from the Koran. The teachings of Sufism is a heresy that led to the decline of Muslims. But the reality proves that al-Quran as a guide to human life not only speaks to the human intellect alone, but also to his heart. If the Koran is only understood through reason, there will be a spiritual drought in the Shari'ah. If the Koran is only understood through a careful approach course there will be inbalance in shari'ah. The mystics with a popular interpretation to the term interpretation isyari try to capture the messages of God in Sufi words (isyari). One among many is traveller Sufi Ibn 'Arabi. Ibn 'Arabi tried to understand the word of God as a whole and integral. In addition, he also includes figures who gave birth to the Sufi teachings are considered controversial in the history of intellectual Islam that is wahdat al-wujud (Existence in Unity). The question then arises as to how the figure of the model interpretation of Ibn 'Arabi is. To answer it, then a research was done. With the known mode of interpretation of Ibn 'Arabi, it can also be shown that the method used in Ibn' Arabi in interpreting the Koran and how the validity of the teachings of Ibn 'Arabi as a result of the interpretation of the Koran. The conclusion of the study is that: Tafsir Ibn 'Arabi emphasizes aspects of the inner meaning of (esoteric) by not ignoring the aspect of birth (exoteric). The style of commentary of Ibn 'Arabi al-llaun including al-isyari. Method of interpretation of Ibn 'Arabi tend to manhaj al-maudu'i (thematic method). Model interpretation of Ibn 'Arabi is methodologically and also substansis. Wahdat al-Wujud is the result of the interpretation of many verses not a wild idea that has no foundation.